Makna Poligami dalam Al-Qur’an dan Penafsirannya di Kalangan Perempuan Penghafal Al-Qur’an - Afib Riza; Muhammad Yusuf Siddik; Umar Farouq; Derysmono Derysmono (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This article examines the meaning of polygamy in the Qur’an and its interpretation among women who memorize the Qur’an. The study departs from the social reality that polygamy is legally and religiously recognized under strict conditions, yet it often generates misunderstanding, family conflict, and psychological tension when practiced without justice, transparency, and adequate religious knowledge. Using a descriptive qualitative method with a phenomenological approach, the research was conducted at STAI DI Al-Hikmah Jakarta from January to March 2024 through observation, interviews, and literature study. The primary data were obtained from two female Qur’an memorizers, while the secondary data were drawn from books, journal articles, laws, tafsir works, and relevant Islamic legal sources. The findings show that the informants interpret polygamy as a permissible practice in Islam, but not as a command or an unrestricted right. Its legitimacy depends on justice, economic capability, mental and spiritual readiness, the consent of the first wife, and urgent or socially responsible reasons. Polygamy that is motivated merely by desire tends to threaten family harmony, whereas polygamy guided by religious ethics and legal procedures may be understood as an exceptional solution.